Psychopharmacology Training and Canadian Counsellors: Are We Getting What We Want and Need? - Schaefer, David; Wong-Wylie, Gina (Canadian Journal of Counselling and Psychotherapy, 2008)
The psychopharmacology training experiences and attitudes of Canadian counsellors were the focus of our national Internet-based survey. This study was part of a larger investigation on Canadian counsellors’ attitudes, practices, and training experiences related to clients on antidepressants. Results of the current study indicate Canadian counsellors vary considerably in type and amount of psychopharmacology training received. A majority of participants reported that they did not receive this type of training in graduate school, though a strong majority advocated for such training to be mandatory in graduate school. Limitations of this research and directions for future research are provided.